Single Stack Active Region Nonlinear Quantum Cascade Lasers for Improved THz Emission - Frederic Demmerle; Jochen Bissinger; Wolfhard Oberhausen; Dominik Burghart; Jonas Krakofsky; Hannes Schmeiduch; Gerhard Boehm; M.-C. Amann (IEEE Photonics Journal, 2017)
We present a single stack active region design for terahertz emission by difference frequency generation in quantum cascade lasers. The active region contains a single design, which is based on multiple optical transitions within one period. This results in both a giant nonlinearity and an ultra-broad optical gain. The provided optical gain spectrum is broad enough to support two distinct mid-infrared modes with a significant spectral separation. For dual-emission, the waveguide contains a buried, index-coupled distributed feedback grating. This grating is based on a sampled approach to provide selective feedback for two mid-infrared modes at λ1=8.39 μm and $λ _{{\text{2 }}}= {\text{9.38}}\, μ {\text{m}}$ . Simultaneously, the manifold of possible transitions within the active region is designed to provide a peak nonlinear susceptibility of $\vert χ ^{(2)}{\rm{\vert \, \,= \,\,}} {\text{29 nm}} {\text{V}}^{- 1}$ at the conversion to 3.8 THz. The device emits up to 210-μW THz power at room temperature with a nonlinear conversion efficiency of $η ={\text{ 2.05 mW}} {\text{W}}^{- 2}$ .